2020
DOI: 10.1038/s41467-020-18125-0
|View full text |Cite
|
Sign up to set email alerts
|

Dual roles of neutrophils in metastatic colonization are governed by the host NK cell status

Abstract: The role of neutrophils in solid tumor metastasis remains largely controversial. In preclinical models of solid tumors, both pro-metastatic and anti-metastatic effects of neutrophils have been reported. In this study, using mouse models of breast cancer, we demonstrate that the metastasis-modulating effects of neutrophils are dictated by the status of host natural killer (NK) cells. In NK cell-deficient mice, granulocyte colony-stimulating factor-expanded neutrophils show an inhibitory effect on the metastatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 68 publications
3
89
0
Order By: Relevance
“…With the help of neutrophil extracellular trap formation (NETosis), tumor cells can even escape immune surveillance. [15][16][17][18] Previous researches suggested that neutrophils may have heterogenous immunophenotypes with dynamic functional plasticity. For instance, once stimulated by transforming growth factor-β (TGF-β), resident tumor-associated neutrophils could polarize into N2 phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…With the help of neutrophil extracellular trap formation (NETosis), tumor cells can even escape immune surveillance. [15][16][17][18] Previous researches suggested that neutrophils may have heterogenous immunophenotypes with dynamic functional plasticity. For instance, once stimulated by transforming growth factor-β (TGF-β), resident tumor-associated neutrophils could polarize into N2 phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…S2b, c ). Mature NK cells can have a major role in controlling B16F10 lung colonization 25 , and then we studied the effect of NK cells by injecting NK1.1 antibody 26 28 . As expected, depletion of NK cells leads to an increase of the lung colonization of B16F10 tumor cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, neutrophils exert immunosuppressive effects on T cells by producing H 2 O 2 , thereby decreasing CD3ζ chain and cytokine expression [ 57 , 58 ]. Additionally, neutrophil derived H 2 O 2 is capable of inhibiting natural killer (NK) cell function which decreases tumor clearance as well as promotes lung colonization in a mouse model of breast cancer metastasis [ 28 , 59 , 60 ]. However, neutrophil-produced ROS can also impair the proliferation of γδ-T cells, thereby decreasing the production of the pro-tumorigenic cytokine IL-17 [ 61 ].…”
Section: Impact Of Tic-produced Ros On Local Tumor Growth and Metastasismentioning
confidence: 99%